2022
DOI: 10.1186/s13012-022-01227-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining the complementarity between the ERIC compilation of implementation strategies and the behaviour change technique taxonomy: a qualitative analysis

Abstract: Background Efforts to generate evidence for implementation strategies are frustrated by insufficient description. The Expert Recommendations for Implementing Change (ERIC) compilation names and defines implementation strategies; however, further work is needed to describe the actions involved. One potentially complementary taxonomy is the behaviour change techniques (BCT) taxonomy. We aimed to examine the extent and nature of the overlap between these taxonomies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Moreover, some of the clusters in ERIC [ 40 ] are clearly directed towards the action target (e.g., Train and educate stakeholders or Support clinicians) , making the coding even more challenging. Our observations are in line with other studies that have highlighted some discrepancies concerning the level of detail across different ERIC strategies [ 7 , 54 , 55 ]. We also acknowledge that other ways of clustering ERIC strategies have been applied in other research initiatives to suit different study objectives [ 2 , 7 , 8 , 10 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, some of the clusters in ERIC [ 40 ] are clearly directed towards the action target (e.g., Train and educate stakeholders or Support clinicians) , making the coding even more challenging. Our observations are in line with other studies that have highlighted some discrepancies concerning the level of detail across different ERIC strategies [ 7 , 54 , 55 ]. We also acknowledge that other ways of clustering ERIC strategies have been applied in other research initiatives to suit different study objectives [ 2 , 7 , 8 , 10 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, it is unknown if we would have received other results if we had coded the data based on another taxonomy. Future studies could investigate how de-implementation strategies differ depending on which taxonomy is used to code the strategies (e.g., [109]).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…ERIC includes multifaceted strategies that combine multiple discrete strategies and strategy bundles and ERIC strategies are variably specified (e.g., some include the actor and dose and others do not), which impacted interpretation. While there is a push for focusing on the mechanisms underlying the strategies [ 19 22 ], we found that clinicians wanted concrete, relatable activities to respond to. The same strategies can be used for different purposes, and different strategies may be targeting the same mechanism of behavior change.…”
Section: Discussionmentioning
confidence: 99%